Scoping review of common bacterial organisms causing vaginal discharge and their antibiotic susceptibility profile in Indian subcontinent - Radhika, A. G.; Gupta, Chhavi; Priyanka, K. Yamini; Sinha, Anju; Malhotra, Rajeev K.; Shiromani, Kushagra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Vaginal discharge (VD) is a major public health issue in the Indian subcontinent, where rising antimicrobial resistance (AMR) compromises syndromic case management (SCM). This scoping review maps the bacterial etiologies of VD and their antibiotic susceptibility across the Indian subcontinent. Based on the CoCoPop framework, a systematic search was conducted on PubMed, Scopus, Embase, Cochrane Library and Google Scholar up to 15 March 2025. Data was extracted from 107 eligible studies involving 37,846 women. Majority of women were from low socioeconomic status. Pathogens isolated amongst symptomatic women included Gardnerella vaginalis (0.38-74%), Staphylococcus sp. (0.9-52.5%), Mobiluncus sp. (4.29-42.13%) and Neisseria gonorrhoeae (0.14-40.34%). In asymptomatic women, Peptostreptococcus sp. (66.67%), Bacteroides sp. (33.33%), Streptococci sp. (25.64%) were identified. Diagnosis relied primarily on microscopy and culture over molecular methods. The key pathogens demonstrated moderate to high sensitivity to Penicillins, Tetracyclines, Macrolides, Sulfonamides and Fluoroquinolones. High sensitivity was reported for Cephalosporins against N. gonorrhoeae (89.5%) and Metronidazole (71%) against G. vaginalis. Aminoglycosides, Beta-Lactam/Beta-Lactamase Inhibitor combinations and Carbapenems demonstrated >70% sensitivity against resistant bacteria including S. aureus, E. coli, Pseudomonas sp. Antibiotic data on anaerobes and MIC data was scarce. High resistance rates challenge the efficacy of standard treatment kits. A strategic shift integrating affordable diagnostics with evidence-based regimens tailored to regional microbial resistance data optimizing treatment and combat antimicrobial resistance is essential.